Sociability: The key to sensory processing disorder - Fotoglou, Anestis; Moraiti, Ioanna; Stergios, Vasilis; Ashley, Paraskevi Elizabeth; Vogindroukas, Ioannis; Speis, Phoebe Demeter; Papantoniou, Stamatina; Chrysouli, Katerina; Karabatzaki, Zoe; Stathopoulou, Agathi (Brazilian Journal of Science, 2023)
Social communication and sensory processing disorder are two factors that interact with each other and the difficulties they find in them impact on different neurodevelopmental disorders such as autism. More specifically, sociability is shown to play a key role in dealing with sensory processing difficulties and the interventions related to it can be implemented in a school setting as well within a therapeutic setting and even at home. The design of these interventions with a focus on sociability aims on the one hand to reduce sensory difficulties and on the other hand to provide meaningful communication when working with children with autism or severe or generalized learning difficulties. This article’s goal is to compile research findings regarding the impact of sociability on children with sensory difficulties through a literature review. Specifically, many interventions with pillars the social communication have been studied to help children with autism and other syndromes The outcomes demonstrated a direct link between sociability and sensory processing disorder with interventions and therapeutic programs implemented in many nations with favorable outcomes in many facets of how children with these issues behave. One of the most effective interventions that helps are Intensive Interaction with high contribution to the sensory regulation of children mainly with autism. Students with neurodevelopmental problems were the samples for the interventions' participants. Application of these programs on a weekly basis, two to three times, is helpful in the right direction.